AC conductivity and dielectric behavior of [Cd(phen)2(SCN)2] - Akgul, Unal; Ergin, Zuhal; Sekerci, Memet; Atici, Yusuf (Pergamon-Elsevier Science Ltd, 2007)
The dielectric properties and the AC conductivity of [Cd(phen)(2)(SCN)(2)] were investigated as a function of frequency and temperature. The dielectric properties were studied in the frequency range of 10(3)-10(6) Hz and in the temperature range of 298-588 K. The AC conductivity was found to obey the universal power law. The variation of the exponent s with the temperature has showed that correlated barrier hopping is the suitable model to describe the electrical conduction mechanism of complex material and according to this model, the maximum barrier height was calculated to be 0.28 eV. The values of the electrical activation energy at various constant frequencies were found to be in the range 0.91-0.96 eV (+/-0.01) and determined to decrease with the increment in frequency. It has been observed that both dielectric constant (epsilon') and dielectric loss (epsilon) decrease with the rise in frequency as they increase with the rise in temperature up to a certain temperature value. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: dielectric properties; AC conductivity; complex of 1,10-phenanthroline